2016
DOI: 10.3389/fnins.2016.00219
|View full text |Cite
|
Sign up to set email alerts
|

Movement Sonification: Effects on Motor Learning beyond Rhythmic Adjustments

Abstract: Motor learning is based on motor perception and emergent perceptual-motor representations. A lot of behavioral research is related to single perceptual modalities but during last two decades the contribution of multimodal perception on motor behavior was discovered more and more. A growing number of studies indicates an enhanced impact of multimodal stimuli on motor perception, motor control and motor learning in terms of better precision and higher reliability of the related actions. Behavioral research is su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
117
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 103 publications
(138 citation statements)
references
References 61 publications
(78 reference statements)
7
117
0
3
Order By: Relevance
“…At about 70-80 ms, Mendonca et al 29 draw a closer temporal window for efficient audiovisual integration related to behavioral features compared to Stein and Meredith 10 related to single-neuron neurophysiology of primates. Young et al 32 also demonstrated that synthesized footstep sounds are perceptually processed like ecological footstep sounds on stride length, cadence estimations, and adaptation, supporting the concept of real-time kinematic movement sonification used by Effenberg 21 and Effenberg et al 22 Most of the referenced studies mapped the additional acoustics to distal segments or parts of the acting person (hand or hands, 3,39,40,42 feet, 29 pen-tip, 36,37 hands, and feet). 22 In addition, Vinken et al 17 drafted a mapping-concept explicitly referencing the "effectors' endpoint trajectory" (p. 537) and stated: "Movement sonification was used to transform kinematic data of the distal end effector into the acoustic domain" (p. 539).…”
Section: Research Questionmentioning
confidence: 70%
See 2 more Smart Citations
“…At about 70-80 ms, Mendonca et al 29 draw a closer temporal window for efficient audiovisual integration related to behavioral features compared to Stein and Meredith 10 related to single-neuron neurophysiology of primates. Young et al 32 also demonstrated that synthesized footstep sounds are perceptually processed like ecological footstep sounds on stride length, cadence estimations, and adaptation, supporting the concept of real-time kinematic movement sonification used by Effenberg 21 and Effenberg et al 22 Most of the referenced studies mapped the additional acoustics to distal segments or parts of the acting person (hand or hands, 3,39,40,42 feet, 29 pen-tip, 36,37 hands, and feet). 22 In addition, Vinken et al 17 drafted a mapping-concept explicitly referencing the "effectors' endpoint trajectory" (p. 537) and stated: "Movement sonification was used to transform kinematic data of the distal end effector into the acoustic domain" (p. 539).…”
Section: Research Questionmentioning
confidence: 70%
“…Although Dyer et al . found transient effects of concurrent rhythmic sonification on a bimanual 4:3 shape‐tracing task resolving in a 24‐h retention measure, Effenberg et al . reported persistent effects of dynamic and kinematic real‐time sonification on motor learning of indoor rowing of novices—even beyond effects of rhythmic adjustments.…”
Section: Research On Multisensory Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] Moreover, such a feedback can enrich the develop-ment of perceptomotor representations by amplifying the brain's ability to integrate multiple congruent perceptual streams, therefore aiding in the formation of stable internal feed-forward models. 3,8 Research conclusively suggests that mapping a performer's action with real-time auditory feedback can enhance both the perceptuomotor representations in the brain and motor performance. [8][9][10][11][12] Strong influence of real-time auditory feedback on motor performance was thought to be due to its influence over the proprioceptive modality.…”
Section: Introductionmentioning
confidence: 99%
“…3,8 Research conclusively suggests that mapping a performer's action with real-time auditory feedback can enhance both the perceptuomotor representations in the brain and motor performance. [8][9][10][11][12] Strong influence of real-time auditory feedback on motor performance was thought to be due to its influence over the proprioceptive modality. [13][14][15][16] Hasegawa et al, 16 for instance, reported that training with auditory augmented biofeedback might facilitate the integration of auditory and proprioceptive systems.…”
Section: Introductionmentioning
confidence: 99%